Zoomorphic stone maces and axes in the forest zone of north-eastern Europe - Manifestations of interaction between hunter-gatherers and cattle herding groups in the 3rd millennium BC - Mantere Ville; Kashina Ekaterina (Suomen arkeologinen seura, 2022)
More than 50 animal-headed stone weapons have been found in the forest zone of north- eastern
Europe. These diverse items consist of maces and axes and they represent a variety of animal
species, of which brown bear and Eurasian elk are the most common. In this article, we pres-
ent an up-to-date overview of these finds and discuss their dating and cultural background. We
argue that the animal-headed stone weapons were prestige items that were introduced to the
northern forest zone by cattle herding groups in the 3rd millennium BC. We interpret the items
as manifestations of a new set of pastoralist beliefs, in which masculinity and the bear probably
played a central part.
Oodeja Mikalle: Juhlakirja professori Mika Lavennolle hänen täyttäessään 60 vuotta Odes to Mika: Festschrift for Professor Mika Lavento on the occasion of his 60th birthday Оды Мике: Юбилейный сборник посвященный 60-летию профессора Мики Лавенто